Rosyjski wykładnik modalności epistemicznej „очевид-но” i jego polskie oraz angielskie odpowiedniki - Puk, Maria (Przegląd Rusycystyczny, 2013)
Maria Puk Uniwersytet Rzeszowski, Rzeszów, Poland PRZ.RUS@op.pl РУССКИЕ ПОКАЗАТЕЛИ ЭПИСТЕМИЧЕСКОЙ МОДАЛЬНОСТИ ОЧЕВИДНО И ЕГО ТЕКСТОВЫЕ СООТВЕТСТВИЯ В ПОЛЬСКОМ И АНГЛИЙСКОМ ЯЗЫКАХ Pезюме Статья поcвящена русскому вводному слову очевидно, которое передает значение предположительности сообщаемого факта, и его текстовым соoтветствиям в польском и английском языках. Среди польских эквивалентов преобладают текстовые, a среди английских — словарные. С морфологической точки зрения это: наречия — widocznie, oczywiście, niewątpliwie, obviously, apparently, evidently, probably, clearly, частицы — pewnie, chyba, zapewne, of course, реже глаголы — musiał, sądziła, must, imagine, seem. в обоих описываемых языках значительное количество примеров составляют предложения, в которых переводчик пропустил показатель эпистемической модаль-ности и изменил модальный план предложения. THE RUSSIAN MARKER OF EPISTEMIC MODALITY ОЧЕВИДНО AND ITS TRANSLATIONAL EQUIVALENTS IN POLISH AND ENGLISH LANGUAGES Summary The article discusses the Russian modal exponent очевидно expressing the probability of information and its Polish and English translational equivalents. The textual counterparts predominate among the Polish equivalents, in English the situation is reverse. From the morphological point they are: adverbs — widocznie, oczywiście, niewątpliwie, obviously, apparently, evidently, probably, clearly, particles — pewnie, chyba, zapewne, of course, rarely verbs — musiał, sądziła, must, imagine, seem. The sentences with the skipped marker of epistemic modality constitute a great deal of examples in both described languages.